Usefulness of Interventions Using a Smartphone Cognitive Behavior Therapy Application for Children With Mental Health Disorders: Prospective, Single-Arm, Uncontrolled Clinical Trial - Shinichiro Nagamitsu; Ayumi Okada; Ryoichi Sakuta; Ryuta Ishii; Kenshi Koyanagi; Chizu Habukawa; Takashi Katayama; Masaya Ito; Ayako Kanie; Ryoko Otani; Takeshi Inoue; Tasuku Kitajima; et al. (JMIR Formative Research)
Abstract BackgroundThe prevalence of mental health disorders among children in Japan has increased rapidly, and these children often show depressive symptoms and reduced quality of life (QOL). We previously developed a smartphone-based self-monitoring app to deliver cognitive behavioral therapy (CBT), implemented it in healthy children, and reported its effectiveness for health promotion. ObjectiveThis study aims to examine the usefulness of the CBT app for improvement in depressive symptoms and QOL in children with mental health disorders. MethodsThe participants were 115 children with mental health disorders (eg, school refusal, orthostatic hypotension, eating disorders, developmental disorders, among others) and aged 12‐18 years. The CBT app–based program comprised 1 week of psychoeducation followed by 1 week of self-monitoring. After reading story-like scenarios, participants created a self-monitoring sheet with 5 panels: events, thoughts, feelings, body responses, and actions. All participants received regular mental health care from physicians in addition to the app-based program. To evaluate the participants’ depressive symptoms and QOL, Patient Health Questionnaire for Adolescents (PHQ-9A), Depression Self-Rating Scale for Children (DSRS-C), and Pediatric Quality of Life Inventory (PedsQL) were measured at the beginning of the intervention, and at 2 and 6 months thereafter. Questionnaire for Triage and Assessment with 30 items (QTA30), and Rosenberg Self-Esteem Scale (RSES) were also used to measure their health and self-esteem. Participants were divided into 4 groups on the basis of the PHQ-9A score (above or below the cutoff; PHQ-9A≥5 or PHQ-9A<5) and completion or noncompletion of the CBT app–based program (app [+] or app [-]). The primary outcome was improvement in the DSRS-C score, and secondary outcomes were improvement in other psychometric scales including PedsQL, QTA30, and RSE. A paired-samples t ResultsThere were 48, 18, 18, and 7 participants in the PHQ-9A≥5 app (+), PHQ-9A≥5 app (-), PHQ-9A<5 app (+), and PHQ-9A<5 app (-) groups, respectively. A total of 24 participants dropped out. No improvement in the DSRS-C score was observed in all groups. However, PedsQL scores improved significantly at 2 and 6 months in the PHQ-9A<5 app (+) group (t17Pt17P ConclusionsThe CBT app was useful for improving PedsQL scores of children with mental health disorders. However, a higher-intensity CBT program is necessary for more severely depressed children.